An Implant-Transfer Technique Without Impression Material - Assunção, Wirley Goncalves [UNESP]; Gomes, Erica Alves [UNESP]; Delben, Juliana Aparecida [UNESP]; Santos, Paulo Henrique dos [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Tabata, Lucas Fernando [UNESP] (Lippincott Williams & Wilkins, 2010)
Different transfer impression techniques for implant-supported prostheses have been suggested to obtain a working cast. This article describes and illustrates clinical and laboratory pros-thodontic procedures to transfer implant positions with splinted transfer copings and without impression material to form a laboratory analog transfer template. With this technique, a preliminary cast is modified to place the analogs according to a corrected position and obtain the master cast. Although this technique does not record adjacent tissues, it is a simple procedure, less time consuming, and easily performed.
Keywords: Implant-transfer technique; dental implant; impression technique; dental prosthesis